The effect of national service of public university matriculation - Puah, Albert Beng Hong (2015)
Existing studies on the effects of conscription on an individual’s university enrolment have produced findings with varying results. In addition, existing studies on the impact of peer effects on an individual’s college enrolment decision often cite a lack of appropriate dataset to effectively quantify its impact on an individual’s university enrolment decision to be the main limitation. Our paper seeks to find out both impacts of conscription and its institutional peer effect on public university matriculation outcome, by utilizing both conscription policy and meritocratic admission into public universities as natural experiments for our study. We find that an applicant who served National Service is 9.8% more likely to matriculate successfully into a public university. However, institutional peer effect does not have any significant impact on public university matriculation outcome.